Effect of Aqueous Extract of Green Tea on Gene Expression of CYP17, CYP11A, LH Beta subunit and LHr Genes in Males Wistar Rats Exposed to Oxidative Stress by Streptozotocin - Muntasser Alawi Awad; Firas Hasan Hadi (Journal of Madenat Alelem University College, 2019)
The present study aims to investigate the beneficial effect of green tea to improve the reproductive system efficiency in adult males rats exposed to the oxidative stress by Streptozotocin. Forty adult male Wistar rats divided randomly to four equal groups , and gavage as following : control group (C) was given drinking water only, second group (T1) : given green tea extract in a dose 100 mg/kg for 60 days. The third group (T2): injected streptozotocine (STZ) by single dose of 60 mg/kg by intraperitoneal (IP) injection. The fourth group (T3) : injected STZ in single dose 60 mg/kg by IP injection then after 30 days were given green tea extract in a dose of 100 mg/kg for 30 consecutive days. In the end of the experiment all animals were sacrificed, samples of testis were taken for study gene expression of CYP11A1,CYP17 and LHr gene ,also samples of pituitary gland were taken for study gene expression of LH beta subunit gene. The results showed there was significant increase (p≤0.05)in fold change of gene expression levels of (CYP11A1,CYP17, and LHr gene) in T1 group compared with control group. Also there was significant decrease (p≤0.05) in fold change of gene expression levels of (CYP11A1and CYP17) in T2 compared with control group. And there was significant increase in fold change of gene expression levels of LH beta subunit gene in T2 compared with other groups. While LHr gene not show significant differences in the C and T2 groups . Also there was significant increase (p≤0.05)in fold change of gene expression levels of (CYP11A1,CYP17 and LHr gene) in T3 compared with T2. It could be concluded that green tea causes up regulation to gene expression of CYP11A1 ,CYP17, LH beta subunit, and LHr in adult males Wister rats exposed to the oxidative stress by STZ.